1987
DOI: 10.1136/bmj.295.6607.1165
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin treatment of IgA nephropathy: a short term controlled trial.

Abstract: Cyclosporin's known regulatory effects on the immune system suggest that it may be useful in treating patients with IgA nephropathy. A randomised prospective single blind study of 19 patients with IgA nephropathy and proteinuria (>1-5 g/day) was conducted to determine the therapeutic value of cyclosporin. The patients were divided into two groups: nine patients were given oral cyclosporin (5 mg/kg/day) for 12 weeks and 10 patients a placebo. The two groups were comparable in age of presentation, ratio of men t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 13 publications
0
35
0
1
Order By: Relevance
“…55,56 None of the evidence is sufficient at present to suggest their use in IgAN patients. Of note, as discussed below, neither cyclosporine A, tacrolimus, or sirolimus prevent recurrence of IgAN in a renal graft.…”
Section: Other Immunosuppressive Monotherapy Approaches Are Not Estabmentioning
confidence: 99%
“…55,56 None of the evidence is sufficient at present to suggest their use in IgAN patients. Of note, as discussed below, neither cyclosporine A, tacrolimus, or sirolimus prevent recurrence of IgAN in a renal graft.…”
Section: Other Immunosuppressive Monotherapy Approaches Are Not Estabmentioning
confidence: 99%
“…ИТ даёт преимущества, так как действует на не-сколько звеньев патогенеза, но всегда следует учитывать её токсические эффекты. Целевые Т-клеточные препараты, например циклоспо-рин, могут уменьшить ПУ в комбинации с ГК посредством клубочковой вазоконстрикции, но они ухудшают клубочковую фильтрацию [49].…”
Section: казанский медицинский журнал 2017 г том 98 №5unclassified
“…However, currently, there are few randomized controlled trials (RCTs) of CsA treatment in patients with IgAN. In 1987, Lai et al reported that treatment with CsA (5 mg/kg) effectively reduces proteinuria, increases serum albumin and partially lowers plasma IgA, although, in that study, the serum creatinine (Scr) level increased in association with a decline in glomerular filtration rate (GFR) in the patients with IgAN (15). Since then, a few non-controlled small sample studies have reported that CsA is effective in treating IgAN without causing significant effects on the renal function (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%